2020
DOI: 10.3390/ani10061017
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Productive Performance in Grow-Finisher Pigs Using Birth and Weaning Body Weight

Abstract: This study aimed to (1) investigate the effect of birth and weaning body weight (BW) on performance indicators of grow-finisher pigs and (2) estimate birth and weaning BW cut-off values in order to identify slow growing pigs (SGP). Pigs (n = 144) were classified as SMALL (0.9 ± 0.13 kg) or BIG (1.4 ± 0.20 kg) at birth and re-classified as SMALL (5.4 ± 1.6 kg) or BIG (6.3 ± 1.91 kg) at weaning. Individual BW was recorded bi-weekly, and feed intake was recorded on a daily basis. Average daily gain (ADG) and feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 51 publications
(92 reference statements)
2
24
0
1
Order By: Relevance
“…Recently, Montoro et al [ 8 ] showed similar findings, as they found that birth BW has a low capacity to act as a predictor of subsequent growth until slaughter, mainly because BW categories can change throughout lactation. Furthermore, similar results were observed when suitable and practical indicators of early carcass depreciation were determined, and the conclusion was that BW could be a valid predictor at the end of nursery [ 7 ].…”
Section: Introductionmentioning
confidence: 80%
“…Recently, Montoro et al [ 8 ] showed similar findings, as they found that birth BW has a low capacity to act as a predictor of subsequent growth until slaughter, mainly because BW categories can change throughout lactation. Furthermore, similar results were observed when suitable and practical indicators of early carcass depreciation were determined, and the conclusion was that BW could be a valid predictor at the end of nursery [ 7 ].…”
Section: Introductionmentioning
confidence: 80%
“…However, delaying weaning up to 49 d of age did not improve performance as this group of pigs (cohort 4) continued to grow slower and kept being delayed throughout the successive stages. Indeed, Camp Montoro et al [ 26 ] observed that pigs with a body weight < 3.7 kg at 28 days of age would require approximately 20 days more to reach target body weight (i.e. 110 kg) compared with pigs over that threshold.…”
Section: Discussionmentioning
confidence: 99%
“…110 kg) compared with pigs over that threshold. Nonetheless, Camp Montoro et al [ 26 ] reported that such pigs had similar feed conversion ratio to their bigger counterparts without any delays or special attention [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations